Accuracy of Platelet Count in Assessing Severity of Preeclampsia (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: The present cross-sectional study was conducted to determine whether platelet count can predict the severity of preeclampsia (PE) with fair degree of accuracy.Methodology: The study was carried out at Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka between January 2013 to December 2013 on admitted preeclamptic women. Preeclamptic women ranging between 20-35 years, gestational age between 28-40 weeks and systolic pressure 140 mmHg and/or diastolic pressure 90 mmHg with proteinuria were the study population. A total of 96 preeclamptic women meeting the enrollment criteria were included in the study. Of them 76 had severe preeclampsia and 22 had mild preeclampsia. Platelet count below 1,50000/mm3 of blood was considered low in this study.Result: Over one-quarter (27.1%) of the patients were < 20 years, 43.8% (20 - 30) years and 29.2% 30 years old with mean age of the patients being 24.9 years. Over three-quarters (77.1%) of the patients belonged to middle class and 22.9% to lower class. Majority (79.2%) of the women was at term pregnancy with ratio of primigravida and multigravida being roughly 2:3. Eight (8.3%) patients had past history of PET. Over one-third (37.5%) of the patients had systolic blood pressure 160 mmHg and 27.1% had diastolic blood pressure 110 mmHg. About 64% of the patients had anemia and 73% had severe proteinuria (albumin 3+). More than 20% of the severe preeclamptics had low (< 1,50,000 per cu-mm of blood) platelet count as opposed to 9.1% of the mild preeclamptic group. The risk of having low platelet count among severe preeclamptics was found to be more than 2-fold (95% CI = 0.5 -12.1) than their mild preeclamptic counterparts (p = 0.037).Conclusion: The study concluded that, platelet count tends to fall as severity of preeclampsia increases. However, platelet count alone cannot predict the severity of preeclampsia as majority of the severe preeclampsia bears platelet within normal range.Ibrahim Cardiac Med J 2014; 4(2): 21-25